A stakeholder theory approach to creating value in higher education institutions. Issue 4 (7th July 2020) - Langrafe, Taiguara de Freitas; Barakat, Simone Ruchdi; Stocker, Fabricio; Boaventura, Joao Maurício Gama
Abstract : Purpose: This paper aims to empirically verify whether the development of improved relationships between higher education institutions (HEIs) and their stakeholders based on the principles of stakeholder theory creates more value. Design/methodology/approach: The methods involve a quantitative approach, with the data collection being carried out through a survey of 88 heads of HEIs in Brazil. The paper uses the Spearman's correlation coefficient to analyze the data and test the hypotheses. Findings: The findings reinforce the arguments found in the stakeholder theory literature, in which relationships are based on the following principles: knowledge and information sharing, mutual trust, involvement in the decision-makin g process and alignment of stakeholders' interests in the strategic planning process, all of which create more value for organizations. Practical implications: This study seeks to improve the knowledge of stakeholder theory in relation to HEIs. It identifies the stakeholder relationships that create the most value and have the potential to generate a sustainable competitive advantage. The results can help managers to improve their relationships with stakeholders and may encourage the implementation of practices and policies that consider stakeholders' influence on the strategic direction of HEIs. Social implications: The studies present a social contribution by evidencing the importance of the development of best practices, processes and strategies in the management of educational institutions, which are important actors in the development of society. Originality/value: The originality of this paper is that it empirically tests the principles of stakeholder theory and their relationships with value creation for organizations in the higher education context. Whilst stakeholder theory has been explored in multiples contexts, there is a lack of studies addressing stakeholder management in HEIs.